As percepções dos funcionários sobre as dimensões formais do Programa de controle de uma Instituição Bancária 2003 - Ribeiro, César Tadeu da Rocha (2003)
This work was developed in a financial institution, with the goal of identifying and analyzing the perception of the employees of the areas defined as the resource focus, according the formal dimension of the actual control program implemented in the institution, with the purpose of exploring the vulnerable points and the conflicting related to the increasing of performance of the employee¿s activities and new tools, concepts and news studies case. The work was conducted with the existing base of theories and concepts, following organizational controls, approachs like Elzioni¿s (1964), Amat¿s and Gomes¿s (2001) and Sturdy¿s, Knights¿s and Willmott¿s (1992). The research done was characterized as descriptive because it aims to describe the perceptions, expectations and the employee¿s profiles in the studied organization, such as field research, because it has the objective of promoting interviews and collecting the primary data and documental, because it will also be performed the analysis of the internal documents of the organization. The research also refers to a certain study case with a sectional cut and predominantly quantitative, but with support in quantitative technics for the initial tabulation of data that were analysed afterwords in interpretative form. The characteristics of the financial institution researched of the control program, has been formed predominantly of post-bureaucratic mechanisms focusing in results, in a hegemonic way expanded, of the utility type with strong alienatorian influences in the employees and with low incentive power, related to the increase of the employee¿s compromises. This way, the control program is noticed by the employees as a monitoring mechanism of actions and results, developed only to increase the institution profits, regardless of the impacts of the physical and emotional aspects and increasing, intuitively, the levels of internal dissatisfaction.